Yields and quality of biomasses and grain in Cynara cardunculus L. grown in southern Italy, as affected by genotype and environmental conditions - Ottaiano, Lucia; Di Mola, Ida; Impagliazzo, Adriana; Cozzolino, Eugenio; Masucci, Felicia; Mori, Mauro; Fagnano, Massimo (Italian Journal of Agronomy, 2017)
Cardoon is a crop well adapted to Mediterranean climatic conditions that is able to grow also in marginal lands thus reducing competition for land with food crops. It is considered a key crop for bio-refinery since it allows producing different interesting molecules for industrial application. From stems it is possible to obtain large amounts of cellulose, grains are a good source of oil and proteins and roots can be a source of inulin. The aim of this research has been to evaluate the productive levels of different genotypes of cardoon in two different climatic conditions of Mediterranean cropland (a site in the Vesuvius plain and a site in the internal hilly cropland). In both the sites, during 3 years (from 2012-2013 to 2014-2015), three genotypes (Altilis, Gigante e Trinaseed) were cultivated with 2 planting densities (4 and 8 plants per m2). A low input cropping system was adopted (no irrigation and 150 kg ha–1 of N supplied as ammonium nitrate). In flat site (NA-Ac.), lignocellulosic biomass yield was 19 t ha–1 d.m. and grain yield 2.7 t ha–1 on the average of the 3 years period. In the hilly site, biomass yield was similar (20 t ha–1 d.m.) while grain yield was higher (3.9 t ha–1 on the average) as compared to the flat site. As regards biomass composition, an increase of hemicellulose and a decrease of cellulose content were measured in the flat site, maybe as a response of plant to the higher drought stress.